Anti Inflammatory Activity of Lemon Grass Mint Herbal Formulation and Its Mediated Zinc Oxide Nanoparticles - Preethi Raj; S Rajeshkumar; T Lakshmi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: For thousands of years natural products, especially plants and vegetables, have been used to fight against various diseases such as cancer, microbial infections and even neurodegenerative diseases. It has been shown that consumption of plants and vegetables have a direct influence on the proliferation, angiogenesis and metastasis of cancer cells. Materials and methods: The anti-inflammatory activity in lemongrass mint herbal formulation was evaluated by Bovine serum albumin denaturation and egg albumin denaturation assays using standardized protocols. Results: The anti-inflammatory of lemongrass and mint extract in zinc oxide nanoparticles was assessed. It was treated with different concentrations (10-50μl) of lemongrass and mint extract for 24h. Lemon grass and mint ZnO NPs treatment significantly decreased the viability compared to control at 24 h time point. Conclusion: The present data demonstrate that extracts of lemon grass and mint ZnO NPs may inhibit the proliferation of cancer cells and induce apoptosis and could provide protection from oxidative stress diseases due to their high antioxidant molecules content.